Molecular Detection of Pathogenic Microorganisms in Gastrointestinal Infection Patients Using Real-Time Polymerase Chain Reaction (Bangladesh Journal of Infectious Diseases, 2026)
Background: Microbiota are defined as the organisms living within the gastrointestinal tract that coexists in the intestine. Its play an important role in dietary action. This is about bacteria, but there are other species of microorganisms that are causing multiple diseases, ranging from those that are treated quickly to those that are very dangerous and need a long time to treat.Objectives: The study aimed to detect and quantify gastrointestinal (GI) tract microbiota using RT-PCR.Methodology: This was a cross-sectional study. A total of 60 stool samples were collected from individuals presenting with gastrointestinal symptoms at Yarmouk Hospital in Baghdad, between October 2023 to May 2024. Fifty stool samples were taken from patients and 10 from healthy people.  Results: The results were recorded 37 samples diagnosed with various bacteria, 6 samples with parasites, and 6 samples with viruses. The use of Real-Time Polymerase Chain Reaction (RT-PCR) represents one of the most accurate and sensitive approaches for detecting microorganisms constituting the gastrointestinal microbiota.Conclusion: This technique allows not only the qualitative detection of microbial DNA but also provides a semi-quantitative assessment through the Cycle Threshold (Ct) value. Ct is inversely related to the microbial load; lower Ct = higher DNA concentration, whereas higher Ct = lower microbial load.Bangladesh Journal of Infectious Diseases, December 2025;12(2):243-249